“If It Ever Really Hurts, I Try Not to Let Them Know:” The Use of Concealment as a Coping Strategy Among Adolescents With Chronic Pain - Wakefield, Emily O.; Puhl, Rebecca M.; Litt, Mark D.; Zempsky, William T. (Frontiers in Psychology, 2021)
Objective: Despite considerable evidence of chronic pain in adolescents, and its adverse consequences for their health and well-being, less is known about pain-related stigma that these youth face, such as pain disbelief by others. Adolescents with chronic pain may conceal their symptoms as a coping strategy to avoid pain-related stigma, contributing to further social isolation and disruptions in medical treatment. In the current study, we used focus group methodology to examine adolescent motivations for using concealment and the possible benefits and harmful consequences of this form of coping. Materials and Methods: Five focus groups of 3-5 adolescents (ages 12-17) with chronic pain conditions (N=18) were conducted as a part of a larger study to evaluate the impact of, and reaction to, pain-related stigma. Patients were recruited from an outpatient pediatric pain management clinic. Transcripts of focus group sessions were analyzed using directed content analysis for the main study, yielding anticipatory stigma and concealment categories. These categories were then explored using inductive content analysis for the current study. Results: Adolescents described engaging in concealment of their pain symptoms. Our analysis revealed three social motivations for concealment: (1) avoidance of judgment; (2) avoidance of being a social burden; and (3) desire to be treated normally, and two harmful consequences of concealment: (1) social isolation and (2) cognitive burden. Conclusions: Disbelief of pain symptoms may exacerbate the social isolation and disease-related burden in this population. Clinical implications of concealing pain symptoms are discussed, and points of intervention are proposed.